Peanut butter consumption patterns of middle-income families in Northern Luzon and Metro Manila - Cabagnot, Rina Judea L; Galvezm Flor Crisanta F. (1999., 1999)
A survey was conducted among urban and rural middle-income families to determine their general background, consumption of peanut butter, peanut butter preferences, and awareness/knowledge of Vitamin A fortification. A total of 76 respondents participated in the survey, with 38 from Northern Luzon (NL) and another 38 from Metro Manila (MM). Results show that most respondents in Northern Luzon and Metro Manila consider the nutritional value of foods as the most important when buying foods and packaging as the least important. Majority of respondents in both regions considers taste as the main basis for choice of peanut butter. Most Northern Luzon respondents buy locally made peanut butter as opposed to only 58% for Metro Manila respondents. 13% of MM respondents buy imported peanut butter while only 3% of Northern Luzon respondents buy imported peanut butter. 50% respondents in NL buy branded peanut butter while about 66% in MM buy branded peanut butter. A higher percentage (76%) of NL respondents buys peanut butter with firm texture, as opposed to only 61% for MM respondents. 5% of NL respondents buy both types of peanut butter. Most of the members of the families who consume peanut butter regularly eat 1 tbsp. or more of peanut butter per snack meal. Results also show that about 95% of the respondents from both regions are aware of vitamin A-fortified foods and are buying them but only about half of the respondents have knowledge about the function of vitamin A in the body. Most of them are willing to buy vitamin A-fortified peanut butter even if the price would increase.
Thesis (BSFT)-- University of the Philippines Diliman
Keywords: Food consumption -- Philippines -- Northern Luzon; Food consumption -- Philippines -- Metro Manila; Peanut butter